2021
DOI: 10.1111/dth.15059
|View full text |Cite
|
Sign up to set email alerts
|

Ocular adverse events in patients with atopic dermatitis undergoing treatment with dupilumab: An Italian single‐center experience

Abstract: Ocular comorbidities are more frequent in patients with severe atopic dermatitis (AD) compared to general population. Dupilumab, a fully human monoclonal antibody that prevents the signaling of interleukin (IL)‐4 and IL‐13, is reported to be efficacious and safe for the treatment of moderate‐to‐severe AD, asthma, and chronic sinusitis. However, conjunctivitis was the most common side effect observed both in clinical trials and real‐life studies in atopic patients. In our experience, among all patients treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
4
4
0
Order By: Relevance
“…Of note, no cases of conjunctivitis were reported in patients who received spesolimab, in contrast to what has been observed in previous clinical trials with other therapies in moderate-to-severe AD. 29,30 These safety findings are in line with previous studies of spesolimab in healthy volunteers and in patients with GPP or PPP. [17][18][19]26 The primary endpoint, percentage change from baseline in EASI at Week 16, between placebo and spesolimab groups (25.6%; p 0.149) was not statistically significant.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Of note, no cases of conjunctivitis were reported in patients who received spesolimab, in contrast to what has been observed in previous clinical trials with other therapies in moderate-to-severe AD. 29,30 These safety findings are in line with previous studies of spesolimab in healthy volunteers and in patients with GPP or PPP. [17][18][19]26 The primary endpoint, percentage change from baseline in EASI at Week 16, between placebo and spesolimab groups (25.6%; p 0.149) was not statistically significant.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, spesolimab was well tolerated, and its safety profile was comparable to that of placebo, with no new or unexpected safety signals observed. Of note, no cases of conjunctivitis were reported in patients who received spesolimab, in contrast to what has been observed in previous clinical trials with other therapies in moderate‐to‐severe AD 29,30 . These safety findings are in line with previous studies of spesolimab in healthy volunteers and in patients with GPP or PPP 17–19,26 …”
Section: Discussionsupporting
confidence: 87%
“…Across the clinical development programme 1% (2/217) of patients discontinued dupilumab therapy due to DAOSD, 3 and a further 1.4% (3/217) patients who had experienced DAOSD withdrew from dupilumab therapy because of conjunctivitis‐related adverse events in the 3‐year open‐label extension study 5 . Similar outcomes have been observed in the BioDay registry data, with 2.4% (5/210) of patients discontinuing therapy due to conjunctivitis, 48 and in recent larger real‐world observational case series the majority of patients who experienced DAOSD remained on dupilumab therapy [range 84–100%] 12,39,49 . It is now accepted that, where possible, discontinuation of dupilumab should be avoided 15,23,55–58 .…”
Section: Resultssupporting
confidence: 62%
“… 5 Similar outcomes have been observed in the BioDay registry data, with 2.4% (5/210) of patients discontinuing therapy due to conjunctivitis, 48 and in recent larger real‐world observational case series the majority of patients who experienced DAOSD remained on dupilumab therapy [range 84–100%]. 12 , 39 , 49 It is now accepted that, where possible, discontinuation of dupilumab should be avoided. 15 , 23 , 55 , 56 , 57 , 58 Several authors support a multidisciplinary management approach.…”
Section: Resultssupporting
confidence: 58%
“…Previous literature reported that prolonged dose interval was effective and safe in patients with stable disease, also leading to both improvement of patient's adherence and reduction of costs 5 . On the other hand, it has been reported that interval prolongation improved dupilumab‐associated conjunctivitis 6,7 …”
Section: Introductionmentioning
confidence: 99%